Two new species of Nitzschia (Bacillariophyta) from shallow wetlands of Peninsular India - Alakananda, B.; Mahesh, M. K.; Hamilton, Paul B.; Supriya, G.; Karthick, B.; Ramachandra, T. V. (Phytotaxa, 2012)
The majority of species belonging to the genus Nitzschia are distinguished by minute taxonomic features that are difficult to observe and document. Currently, geographical distributions for many species are recognized as cosmopolitan; in contrast endemic species are poorly documented and studied. Our study describes two new species of Nitzschia from shallow wetlands across the Bangalore urban district of peninsular India, Nitzschia taylorii, sp. nov. and Nitzschia williamsi, sp. nov. Morphological analyses of these new species were performed with light and scanning electron microscopy, and the ecology of inhabited wetlands are discussed briefly. New species records from urban polluted wetlands provide evidence for broadening taxonomic and ecological investigations of cosmopolitan genera like Nitzschia in the Southern Hemisphere.